Attitudes of Special Education Teachers towards Evidence Based Practices and Obstacles to Its Application - Soultanh Alotaibi (Umm Al-Qura University, 2022)
The current study aimed to identify the attitudes of special education teachers towards evidence-based practices and discover the difference in their attitudes according to the following variables (type of specialization, educational stage, educational qualification, training), as well as discover the obstacles that prevent their application. To achieve these goals, the descriptive approach was used, which relied on the questionnaire as a tool for collecting data from the study sample of (314) female teachers. The results found that special education teachers have positive attitudes towards evidence-based practices, and the results also found that there is no difference between special education teachers' attitudes towards evidence-based practices according to the variable of specialization, academic qualification, and educational stage, with the exception of training that resulted in a difference in attitudes in favor of the teachers who attended training courses. One of the main obstacles that prevent special education teachers from applying evidence-based practices was the lack of financial support allocated to provide the tools and devices needed to use evidence-based practices, limited communication between researchers and teachers to inform them of the most important evidence-based practices, and the lack of available sources for evidence-based practice.